2001
DOI: 10.1038/emm.2001.23
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of melanogenesis by glycyrrhizin in B16 melanoma cells

Abstract: Glycyrrhizin (GR), triterpenoid saponin composed of one glycyrrhetinic acid (GA) and two glucuronic acids, is a main constituent of the hydrophilic fraction of licorice (Glycyrrhiza glabra) extracts and is known to have a wide range of pharmacological actions. In this study, we investigated the mechanism of GR effect on melanogenesis in B16 murine melanoma cells. The cellular levels of tyrosinase mRNA, protein, enzyme activities and melanin contents were increased by GR in a dose dependent manner. Expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 24 publications
(19 reference statements)
1
37
0
Order By: Relevance
“…Cells were cultured in DMEM containing 10% FBS, 100 U/ml penicillin, 0.1 mg/ml streptomycin, and 0.25 μg/ml amphotericin B at 37 o C in a humidified 95% air/5% CO2 atmosphere as described previously (Jung et al, 2001). XH was obtained from Alexis Biochemicals (Lausen, Switzerland), and α-MSH, IBMX, and forskolin were obtained from Sigma (St. Louis, MO).…”
Section: Cells and Materialsmentioning
confidence: 99%
“…Cells were cultured in DMEM containing 10% FBS, 100 U/ml penicillin, 0.1 mg/ml streptomycin, and 0.25 μg/ml amphotericin B at 37 o C in a humidified 95% air/5% CO2 atmosphere as described previously (Jung et al, 2001). XH was obtained from Alexis Biochemicals (Lausen, Switzerland), and α-MSH, IBMX, and forskolin were obtained from Sigma (St. Louis, MO).…”
Section: Cells and Materialsmentioning
confidence: 99%
“…The B16F10 murine melanoma cell line was obtained from the Tumor Researching Department of The Third Affiliated Hospital of Harbin Medical University, Harbin, China. Cells were cultured in DMEM containing 10% FBS, 100 U/ml penicillin, 0.1 mg/ml streptomycin, and 0.25 μg/ml amphotericin B at 37˚C in a humidified 95% air/5% CO 2 atmosphere as described previously (11). Drug treatment began 24 h after seeding, and cells were harvested after indicated concertations and times of incubation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that extracts from some herbs, including kava rhizome extract (43), glycyrrhizin (44), lotus flower (45), cubebin (46), quercetin (47) and naringenin (17) increase melanogenesis in B16 melanoma cells and human melanocytes, thereby indicating that natural resources should be extensively screened for the development of gray hair prevention agents or therapeutic drugs to induce repigmentation in the skin of vitiligo patients.…”
Section: Discussionmentioning
confidence: 99%